Analysis on Computer Interlocking Logic Design for Main Line of Urban Rail Transit - LIANG Yun-peng; WANG Cheng; LV Hao-jiong (机车电传动)
Function of computer interlocking equipment, which was considered as one of core subsystem of signal system was discussed. Moreover, in terms of practical requirement, a modified method of interlocking logic realization was proposed. According to the characteristics of urban rail transit, the design principle of application layer software was investigated. Based on the investigation and analysis, the proposed computer interlocking logic design for main line of urban rail transit was expected to meet the requirement of customers and speed up the process of localization of urban rail transit signal system.